Sistema de controle de pêndulo invertido - Pedroso, Caio Cesar de Souza (2017)
The inverted pendulum is a process control model with numerous applications, whether industrial, military, aerospace or for fun. Which knowledge of mechanics, electrical, electronics and process control are crucial for the elaboration of this system. The purpose of the inverted pendulum control system is to maintain the balance of the pendulum structure on two concentrically arranged wheels, as the center of gravity is positioned in the structure and is located above the axis of the wheel pair, the inverted pendulum system is an unstable system because it tends to move away from the equilibrium position very easily. So that the system does not fall nor to one side neither the other, it becomes necessary to apply a force, in the case of torque on the wheels of the pendulum. The system have to be able to detect to which side the disturbance is occurring, to calculate the acceleration of this turning movement and to perform the drive of the motors to correct its unbalance, besides being able to correct the disturbances of the system. Since this is a balance of a mass on its axis of rotation, the system is very susceptible to instability. This work aims to use the knowledge acquired with the subjects of the mechatronics technology course and intends to serve as a tool for the elaboration and construction of an inverted pendulum prototype.